The Effectiveness of Tandem Walks on Reducing the Risk of Falling in the Elderly: A Case Report - Setiawan; Dadang Purnama; Amelia Hayati (HealthCare Nursing Journal, 2023)
The elderly experience physiological decrease, especially in the musculoskeletal, neurological, and sensory systems, which have an impact on changes in body posture, decreased proprioception, and visual impairment. These physiological changes increase the risk of falling in the elderly. Falls are a major cause of severe injury and death among the elderly in the community. Intervention management through tandem walking has been widely studied to have a better impact on reducing the risk of falling than other interventions. This case report aims to determine the effectiveness of tandem walking interventions in the elderly with a diagnosis of fall risk in the community.This case uses a case report involving one elderly person in a community with a high risk of falling category. The tandem walking intervention was carried out for ten days at least once a day, and a Tinetti Gait and Balance test was carried out to see the fall risk category before and after the tandem walking intervention was given. After being given the tandem walking nursing intervention for ten days, although there was no change in the fall risk category, there was a decrease in the Tinetti Gait and Balance score compared to before the intervention. In addition, the elderly said that after doing tandem walking, their walk was more balanced, and they did not need assistance when walking by holding the wall around it like before. The results of this case report only involved one elderly, but the interventions provided can reduce this bias because they can reduce the risk score of falling Thus, case report can be used as an initial study for further research related to modification of tandem roads in the context of the elderly population in a larger sample with a true experiment design.